Conservation Strategy Proposal for Antakya Historic City Centre after 2023 Kahramanmaraş Earthquake - Filiz Karakuş; Esra Koyuncu (Proceedings of the International Conference of Contemporary Affairs in Architecture and Urbanism-ICCAUA)
This article investigates the damage to registered buildings in the Antakya urban site following the Kahramanmaraş earthquakes, offering preservation recommendations based on a holistic approach that considers the buildings’ physical features, historical background, social memory, and ties to local life. There is a notable gap in comprehensive, locally focused post-disaster conservation studies for Antakya in the existing literature; this research aims to fill that gap. The methodology includes data collection, field observation, documentation, evaluation, and proposal development. Damage assessments were conducted on 250 buildings using the 1997 Umbria-Marche earthquake damage classification and methods developed by the Turkish Catastrophe Insurance Pool in 2002. Findings show that 131 buildings collapsed, while others suffered varying degrees of damage. The study highlights the importance of resilient conservation strategies grounded in international principles and supported by disaster risk management, holistic preservation, Building Information Modeling, and Integrated Project Delivery. Conducted seven months after the earthquake, this research documents original damage patterns at risk of being lost due to restoration and interventions, providing early and valuable data to the literature. As one of the first comprehensive studies to systematically examine earthquake damage to Antakya’s historic fabric, it serves as an important reference for future research.